Beta-amyloid and mitochondrial-derived peptide-c are additive predictors of adverse outcome to high-on-treatment platelet reactivity in type 2 diabetics with revascularized coronary artery disease. (25th November 2020) - Ikonomidis, I; Katogiannis, K; Kyriakou, E; Taichert, M; Katsimaglis, G; Tsoumani, M; Andreadou, I; Lambadiari, V; Maratou, I; Kousathana, F; Varlamos, C; Plotas, P; et al.
Abstract: Background and aims: Increased b-amyloid and decreased Mitochondrial-derived peptide (MOTS-c), are reported in diabetes. We investigated their additive value to high on-clopidogrel platelet reactivity (HPR) for adverse outcome in type 2 diabetics after recent revascularization. Patients and methods: In 121 type II diabetics, treated with clopidogrel and aspirin, (93 males, mean age 67.2 years) we measured: a). maximum platelet aggregation to adenosine diphosphate (ADP) by Light Transmission Aggregometry (LTAmax), b) Malondialdehyde (MDA), as oxidative stress marker, c) MOTS-c, d) b-amyloid blood levels. Cardiac death and acute coronary syndromes (MACE) were recorded during 2 years of follow-up. Results: Out of 121 patients, 32 showed HPR (LTAmax >48%, ). At baseline, HPR was associated with b-amyloid >51 pg/ml (p=0.006) after adjusting clinical variables, HbA1c, MOTS-c, MDA and medication. During follow-up, 22 patients suffered a MACE. HPR, b-amyloid >51 pg/ml and MOTS-c<167 ng/ml were predictors of MACE (relative risk 3.1, 3.5 and 3.8 respectively, p<0.05) after adjusting for confounders and medication. There was significant interaction between HPR and b-amyloid or MOTS-c for the prediction of MACE (p<0.05). Patients with HPR and b-amyloid>51mg/dl or HPR and MOTS-c concentration<167 ng/ml had a 4-fold higher risk for MACE than patients without these predictors (relative risk 4.694 and 4.447 respectively p<0.01). The above results were confirmed in an external validation cohort of 90 patients with diabetes and CAD. Conclusions: Increased b-amyloid or low MOTS-c are additive predictors to high on-clopidogrel platelet reactivity for adverse outcome in diabetics with CAD during 2-years follow- up. Funding Acknowledgement: Type of funding source: None